The relationship between leadership styles and safety behavior : a case study of construction industry in Klang Valley - Mohd Zhafri, Harudin (2018)
The purpose of this research is to identify the relationship that exits between the leadership style and safety behavior in Klang Valley in the construction industry. Quantitative research design was adopted for this study. There are a total of 350 sets of questionnaire had been distributed to Econpile Sdn Bhd employee in Klang Valley area. However, total number of 275 sets of questionnaires had been collected. The Cronbach Alpha was used to measure the internal consistency of the questionnaire. Inferential statistical analysis has been used to determine the relationship between transaction, transformation, and situational leadership towards safety behavior such as Pearson Correlation Analysis and Multiple Regression Analyse. In addition, the frequency of descriptive statistics, such as mean, frequency, and standard deviation are used to analyze the relationship (transformation, transaction, and situational) affecting the safety behavior among Econ-pile Sdn Bhd employee. Based from the findings, all independent variable (leadership style) have significant relationship with dependent variable (safety behavior). The correlation result reveals the transnational leadership correlated with highly positive correlation than transformation and situational leadership.